Economic survey of Nigeria 1959 (Lagos : Direction of the National Economic Council, 1959)
The survey has been prepared on the direction of the National Economic Council, and not only will it assist the Council, the Joint Planning Committee, and the government of the Federation in preparing and coordinating development plans and economic policies, but that the survey will also be of considerable value both to Nigerian businessmen and to the rapidly increasing number of overseas businessmen and other persons who are showing a growing interest in Nigeria.
aia 24/04/2017
Loans
Keywords: Economic conditions; Nigeria